A multiple case study on how siblings transform on existing domestic space into a shared study space - Cayanan, Ira Louise F. (College of Home Economics, University of the Philippines Diliman, 2019)
A shared study space is usually not originally planned in the residential house. A time comes when the children would need a study space, and parents must allow for the provision of a space for such purpose. Therefore, this study attempted to determine how the shared study space was transformed and utilized by the siblings. The purposes of this study were to describe the physical environment of the study space shared amongst siblings, to identify factors on how the siblings allocate and utilize the space, and to propose essential factors to consider for a shared study space among siblings. Three middle-class Filipino college students sharing an allocated domestic study space with their siblings were interviewed and observed in the space. Together with their siblings, a total of seven student participants were interviewed for this study. The application of Proxemics through different facets of Filipino culture were explored to determine how siblings used shared study spaces. Sibling relationships and study habits were examined to discern the factors they considered related to the spatial environment. Results showed sibling relationship reflected in the shared study spaces in terms of prioritized designation, ratio of space distribution, degree of territoriality, and interaction within the space. Filipino concepts were observed in the multi-functional quality of the study rooms seen in the furniture layout and its open space planning. Moreover, study habits influenced the activities done in the space. Ultimately, three considerations--functionality, convenience, and economic reason--influenced their decisions in transforming an existing domestic space as seen in the positions of objects and the purposes it served to suit their academic needs.